Studi tentang Kompetensi Guru Agama dalam Membentuk Akhlak Mulia Peserta Didik SMA Negeri 9 Bone (Implementasi PMA RI NO 16 Tahun 2010) - Syah, Marwan (JURNAL AL-QAYYIMAH, 2019)
This thesis discussed about the Study of Religion-subject Teachers’ Competence in buildingthe good attitude of the Learners at SMA Negeri 9 Bone (the Implementation of PMA RI No. 16 Tahun 2010). This research used qualitative research with theology normative, juridical, pedagogical and psychological approaches. The data sources of this research were principal/headmaster, vice principal, teachers of Islamic Education (PAI), BK teachers, and learners. Methods in collecting data were observation, interview, and documentation. Processing and analysing data were done through data reduction, data presentation, and verification. The results showed that: (1) the description about the understanding of Religion-subject teachers’competence in SMA Negeri 9 Bone was theoretically understood and applied in the form of religious teachingactivities, but there was weaknesses in the implementation if it measured by the juridical indicators of the teacher education background that were SI Islamic Education program and Master of Islamic Education.While the development of Islamic teacher’s competence were done through active in MGMP, professional development training, teacher experience in teaching, the roles of the principal in giving motivation to the teachers, and continue their study.(2) the implementation of religion-subject teacher’s competence in building the good attitude of the learners in SMA Negeri 9 Bone could be seen in the ability of religion-subject teachers in carrying out religious teachings activities that started from planning to the implementation.(3) the problems in buildinggood attitude of the learners were limited time of teaching PAI, environmental influences, paradigm of society, facilities and infrastructures, and globalization.While the efforts in building the good attitude of the learners through exemplary, habituation, advice and motivation to the learners, and creating an Islamic culture in the school.